Analisis Implementasi Kebijakan Penghapusan Sanksi Adminitrasi Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Di Kantor Samsat Cibinong Bogor Tahun 2021 - NURANIS SITI RAHAYU; Licke Bieattant (Jurnal Ilmu Administrasi Publik, 2022)
The purpose of this study was to analyze the implementation of the motor vehicle tax administration sanction elimination policy in an effort to increase local tax revenues at the Cibinong SAMSAT office in Bogor in 2021 and to find out the inhibiting factors and efforts of the West Java provincial government in overcoming the problems in the implementation of the motor vehicle tax administration sanction elimination policy in an effort to increase local tax revenues at the Cibinong SAMSAT office Bogor in 2021. This study used a qualitative approach with a descriptive type and data collection techniques in the form of interviewing informants to obtain primary data and documentation to obtain secondary data. The results of this study indicate that based on the data on the number of motorized vehicle taxpayers and data on income recapitulation or motor vehicle tax revenue in 2016-2021, the contribution of the policy of eliminating motor vehicle tax administrative sanctions to the regional tax revenues in 2021 at the Cibinong SAMSAT office in Bogor has fluctuated. Collaboration has been carried out by the Cibinong SAMSAT office in Bogor and several related agencies such as the police, Jasa Raharja, PUSDATIN (Data and Informatics Center), and the Information and Statistics Communications and Statistics Sub-dept, to campaign for policies to eliminate motor vehicle tax administration sanctions. Installation of banners and campaigns in print and internet media have also also carried out to build public awareness. However, there are still obstacles such as the lack of adequate facilities and infrastructure to reach a very wide area with a large number of taxpayers